Política de saúde brasileira e a Fundação Hospitalar de Saúde De Sergipe: implicações para o trabalho do assistente social do HUSE - Magalhães, Anne Gislâyne Amorim (2019)
This research aims to understand how the managerial model of the Sergipe Hospital Health Foundation has focused on the professional daily life of social workers at HUSE / SE. The research will seek the understanding of the object of study from the reality lived in the Emergency Hospital of Sergipe Governor João Alves Filho (HUSE), considering the innovations in the scope of work management in this. The focus of the research in HUSE is justified by the fact that this is the most expressive hospital in the public hospital network of the state, consequently, with significant rebates for the working class, especially the social assistants. Thus, the main objective of the study is to analyze how the organizational and political restructuring of the Sergipe Hospital Foundation affect the work of social workers of HUSE / SE. The method used to understand the object of study will be dialectical historic materialism. Thus, the research will be developed through a qualitative approach that has as its methodological approach the Case Study. For this, we used the documentary and bibliographic research, which allowed the consultation to different sources, such as management report, laws, decrees and semi-structured interview with 12 (twelve) social workers of HUSE that constituted the sample. The data showed that the FHS presents itself as a reflection of the dismantling of public health policy in Sergipe, as well as the inefficiency in the management of work performed by it in HUSE. At the same time, it was highlighted the difficulties faced by HUSE social workers, in their working conditions and in the professional recognition / appreciation within the multiprofessional team and in front of the FHS management. In addition, it was found that it is preeminent and urgent to find ways to enable the strengthening of the profession within the collective work process of health work, valuing and recognizing before each other as a health professional.